Minimization of the Stressed State of a Stringer Plate with a Hole and Rectilinear Cracks - Mir-Salim-zade, M.V. (Проблеми машинобудування, 2019)
This article deals with the problem of minimizing the stress state on the contour of a hole in an un-bounded isotropic stringer plate weakened by two rectilinear cracks. Crack faces are considered to be free of stress. У цій статті розглядається задача мінімізації напруженого стану на контурі отвору в необмеженій ізотропній стрингерній пластині, ослабленій двома прямолінійними тріщинами. Береги тріщин вважаються вільними від навантажень. В данной статье рассматривается задача минимизации напряженного состояния на контуре отверстия в неограниченной изотропной стрингерной пластине, ослабленной двумя прямолинейными трещинами. Берега трещин считаются свободными от нагрузок.